1983
DOI: 10.3177/jnsv.29.545
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal changes in glycogen stores in liver and skeletal muscle of rats in relation to the feed timing of sucrose.

Abstract: SummaryDiurnal changes in tissue glycogen stores were determined in rats in relation to the feed timing of sucrose. Rats were daily meal-fed on a 35% sucrose diet at 20.00-21.00 and a basal diet at 08.00-09.00, or meal-fed on the same diets at the reversed time for 7weeks. Half of the animals were allowed voluntary wheel-running between 21.00-08.00, but the remaining animals were restricted to exercise for 24h. At the end of the feeding period, both groups of rats were killed at 4-h intervals. Glycogen stores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Voluntary running has been employed in rodents as a model of exercise to induce skeletal muscle adaptation (30,45). Although the muscle activity pattern (intermittent bursts of activities) is different from human endurance exercise, such as long-distance running, the observed functional adaptations in skeletal muscle are similar between the animal models and humans in many aspects, which have been characterized in mouse skeletal muscle using various morphological and biochemical analyses (12,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Voluntary running has been employed in rodents as a model of exercise to induce skeletal muscle adaptation (30,45). Although the muscle activity pattern (intermittent bursts of activities) is different from human endurance exercise, such as long-distance running, the observed functional adaptations in skeletal muscle are similar between the animal models and humans in many aspects, which have been characterized in mouse skeletal muscle using various morphological and biochemical analyses (12,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a diurnal rhythm in adipose tissue sensitivity to epinephrine-stimulated lipolysis is highest at the end of the active period in rats. 91 Norepinephrine also functions as an important neurotransmitter in the sympathetic nervous system and has central effects on feeding behavior; administration of hypothalamic norepinephrine suppresses feeding behavior in the dark phase and stimulates feeding behavior in the light phase of rats. 92 …”
Section: Extrinsic Mediatorsmentioning
confidence: 99%
“…In the previous studies, the effects of exercise, performed 8-16 h before (last day) meal intake on postprandial TG concentrations, have been examined; however, information regarding the effects of exercise on the day of a high-fat meal intake is limited, despite the importance of the timing of exercise and meal intake in gaining the benefits of exercise. Several studies have demonstrated that adequate meal timing on the day of exercise is important for glycogen loading, muscle building, and nutrient consumption (6,14,36), mainly due to the modification of hormone responses. The timing of exercise is therefore crucial to obtaining the maximum benefits of exercise and in the establishment of customized exercise programs for treating and preventing common diseases.…”
mentioning
confidence: 99%